Development of 3D Animation Video-Based Learning Media Using SketchUp in Building Construction and Utility Subjects - Mareti Gulo; Envilwan Berkat Harefa; Arisman Telaumbanua; Aprianus Telaumbanua (Universitas Muhammadiyah Enrekang, 2023)
The problems found by researchers through observations of the learning process at SMK Negeri 1 Lotu, namely the learning process using media is still not optimal. The aim is to develop learning media in class XI-DPIB based on 3D animated videos using SketchUp in the subject of Building Construction and Utilities to understand the Feasibility, Practicality, and Effectiveness of Media Products. This type of research uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The instruments used in this research were validation questionnaires for feasibility tests, student response questionnaires for practicality tests, and essay tests to test the effectiveness of learning outcomes. The results of this study are in the form of animated video-based media using SketchUp in the Building Construction and Utilities subject. Very Eligible Criteria based on the assessment of material experts 93%. Based on the assessment of linguists 92%. Based on the design expert's assessment of 90.59%. Practicality The media is categorized as very practical based on 91% individual trials and 93% field trials. The criteria are very effective with an effective percentage of 93% media. So it can be concluded that the 3D animated video-based learning media using SketchUp that was developed is very feasible, practical and effective for use in the learning process. suggestions from researchers (1) for students, it is hoped that the presence of 3D animated video-based media can increase effectiveness and critical thinking in visible image material, (2) for teaching staff it can add innovation in using media (3) for researchers, they can use this research as the next research to determine the feasibility of the product.